2017
DOI: 10.1080/09638288.2017.1368724
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to a changed body. Experiences of living with long-term pelvic girdle pain after childbirth

Abstract: The participants' narratives highlighted that the pain led to severe functional limitations that threatened their capability to perform meaningful daily activities, and interfered with their sense of identity. It appears essential to meet with each patient individually and to manage long-term pregnancy-related pelvic girdle pain as a pain syndrome. IMPLICATIONS FOR REHABILITATION Chronic pregnancy-related pelvic girdle pain • Pregnancy-related pelvic girdle pain impairs women's capacity to perform meaningful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Perspectives on the life-world and the epistemological assumptions of phenomenology points to the particular world of experiences that we know and take for granted, as our life-world is all we know yet it is impossible to know completely (Merleau-Ponty, 2002). In this article, we support and expand the findings of other qualitative researchers in this field (Engeset et al, 2014;Gutke et al, 2017;F. Wuytack et al, 2015b), specifically concerning how the pain and physical challenges complicate women's daily activities, partnerships, family activities and ability to take part in social and working life.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Perspectives on the life-world and the epistemological assumptions of phenomenology points to the particular world of experiences that we know and take for granted, as our life-world is all we know yet it is impossible to know completely (Merleau-Ponty, 2002). In this article, we support and expand the findings of other qualitative researchers in this field (Engeset et al, 2014;Gutke et al, 2017;F. Wuytack et al, 2015b), specifically concerning how the pain and physical challenges complicate women's daily activities, partnerships, family activities and ability to take part in social and working life.…”
Section: Discussionsupporting
confidence: 69%
“…The women who took part in this study explained how, over time, they adapted to the symptoms while going through the slow process of accepting their situation, experiences that are in line with findings from Gutke et al (2017). As ignoring the pain would bring its own punishment, the women found ways to deal with their long-term situation, involving planning for activities, resting and reducing social and physical activity.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A substantial number of qualitative studies addressing how women experienced PGP after childbirth were identified in a preliminary search of the literature. The studies reveal the perspectives of women about living with PGP the effects of PGP and women's need for supportive resources to recover from PGP 5,6,15‐18 . The tension women experience between their pain and their role as a mother is a significant conflict that is not well understood by support system of families and health care providers.…”
Section: Introductionmentioning
confidence: 99%